2022
DOI: 10.1038/s41398-022-02125-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rate of schizophrenia after the Tangshan earthquake in China: a 44-year retrospective birth cohort study

Abstract: Preliminary evidence indicates that natural disasters are associated with an increased risk for schizophrenia. With few longitudinal studies on earthquakes, this retrospective cohort study examined exposure to the 1976 Tangshan earthquake and the subsequent risk of schizophrenia. Population counts and visits to all nine psychiatric hospitals in Tangshan city were collected. We created three cohort groups by earthquake exposure: infant (August 1972 to July 1976 births), fetal (August 1976 to May 1977 births), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…With regard to the first finding, additional studies confirm the increased risk for the development of schizophrenia in offspring prenatally exposed to a (natural) disaster such as an earthquake [ 76 , 77 ], a terrorist attack [ 78 ], infections, and lead exposure [ 79 ]. There are several potential reasons for this effect of unfavorable environmental circumstances on an increased susceptibility to schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the first finding, additional studies confirm the increased risk for the development of schizophrenia in offspring prenatally exposed to a (natural) disaster such as an earthquake [ 76 , 77 ], a terrorist attack [ 78 ], infections, and lead exposure [ 79 ]. There are several potential reasons for this effect of unfavorable environmental circumstances on an increased susceptibility to schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study on the massive 1959-1961 famine in China and its relationship with incidence of schizophrenia found that prenatal exposure to famine increased the risk of schizophrenia in later life (St Clair et al, 2005). More recently, a 44-year birth cohort study found that fetal exposure to the 1976 Tangshan earthquake resulted in a 25% higher risk for developing schizophrenia compared to non-exposure during fetal development (Zhang et al, 2022). In summary, although there have been numerous studies on mental health problems during the COVID-19 pandemic in China, immediate and long-term negative mental health outcomes resulting as an unintended consequence of the country's continuing strict COVID strategy should also be examined.…”
mentioning
confidence: 99%
“…For instance, a study on the massive 1959–1961 famine in China and its relationship with incidence of schizophrenia found that prenatal exposure to famine increased the risk of schizophrenia in later life (St Clair et al, 2005). More recently, a 44-year birth cohort study found that fetal exposure to the 1976 Tangshan earthquake resulted in a 25% higher risk for developing schizophrenia compared to non-exposure during fetal development (Zhang et al, 2022).…”
mentioning
confidence: 99%